Расчет скорости и коэффициента поглощения звука в жидкостях с квазисферическими молекулами - Odinaev, S.; Abdurasulov, A. (Publishing house "Academperiodika", 2019)
A short review of theoretical and experimental works dealing with the research of acoustic parameters of some classical liquids and their solutions is made. On the basis of the analytical expressions obtained in the framework of molecular-kinetic theory for the sound velocity c(v) and the absorption factor a(v), as well as the choice of a model for the potential of intermolecular interaction Φ(|r|) and the radial distribution function g (|r|), the frequency dispersion of acoustic parameters for liquid N2, O2, and CH4 was numerically calculated in wide intervals of density and temperature.